(3GdMbjbIs - (3Ydj Hf CHj WGdH GdbQTj,J (B40 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hHYO hgh bhdg eG dGMbjbI abGd Ydjg GdSdGe eGdc hGdMbjbI s
(3BNQgG (B:s
(3abO WdY Ydjc JHGTjQ fhQ GdMb fhQ GdUHM Edi fhQ GdTeS hbJ GdESJhGA hGddg GdgGOi Edi WQjb GdQTGO s
(3Vef eLehY , JQJjHgG (B: (3GdKdGKhfs
(3GfXQg eY GdeNWhW Qbe (B292s
(3HgG fXGe GdJYbjHIs
(3hgj QSGdI ef cdGe CejQ GdeDefjf Ydi Hf CHj WGdH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B295s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds